“Recent global social movements as a cognitive and practical challenge for the social sciences" - Guibentif, P. (The Futures We Want: Global Sociology and the Struggles for a Better World, 2016)
Today, social sciences, and sociology in particular, have to add to their research agenda the study of what we may call recent global social movements. New social entities are playing an increasing role in our globalized world, apart from states, international organizations, multi-national companies and internationally operating NGOs. What is at stake here, however, is not only to produce knowledge about these entities. It is also to discuss reflexively (Bourdieu) the practical relationship between social sciences and these entities. Indeed, this relationship appears to be rather paradoxical. On the one hand, science plays a role in the processes which lead to the formation of social movements, in the first place economics, but also sociology, notably sociology of social inequalities and theories of globalization. On the other, science is denounced for being an instrument of governance and for producing expert knowledge accessible only to an elite. So this relationship needs to be analyzed as such, and this analysis reopens the old question of the relationship between science and politics, now that new players are participating in the political processes, changing the nature of these processes. This discussion acquires particular complexity in the sociology of law. As a matter of fact, jurisprudence faces a similar challenge, having to rethink the relationship of law and politics. And sociology and jurisprudence both will have to deal with this crucial question raised by these changes in the political processes: is it possible to experience and effectively defend rights without the background of differentiated jurisprudence and science (for different approaches to this topic: Reemtsma, Supiot, Teubner). The paper aims at contributing to this discussion, on the basis of observations and experiences gathered in Portugal during the recent financial crisis, and of a comparison of Portugal with other European countries.